KINERJA PROGRAM KESEHATAN DAN KESELAMATAN KERJA (K3) DI PERUSAHAAN PLYWOOD TAHUN 2012 - 2016 - Nikita Ayu Dwijayanti (Universitas Airlangga, 2018)
PT. Kutai Timber Indonesia (KTI) was a company that belongs to the timber sector. Occupational accident frequently happened on PT. KTI and those ccupational accidents must be reported and recorded to monitor occupational health and safety (OHS) performance program. The aim of this study was to measure OHS performance on PT. KTI in 2012 – 2016 with occupational accident statistic. This research was descriptive study that explained occupational accident statistic and OHS programs in PT. KTI. The statistic of occupational accident that include incident rate, frequency rate, severity rate and safe T-score. The data collection was through secondary data, observation sheets, and questionnaires. The results of this research were 303 occupational accidents that happened since 2012 until 2016. The highest incident based on Statistic calculation of occupational accident were incident rate and frequency rate in 2012, meanwhile the highest severity rate occurred in 2012, 2015 and 2016. Based on safe T-score calculation OHS Performance just increased in 2015.The result of this study was being affected by the OHS programs that had not changed since 2012 until 2016. 3 out of 11 programs had unfulfilled criterias under 50%, those were bus employees, planning and implementation of JSA and implementation of OHS.Keywords: OHS performance,OHS program, statistic of occupational accidents.